Using Problem-based Learning Strategy to Enhance Students’ Speaking Skill in MAN 1 Lubuklinggau - Luthfiyyah, Anggun; Fiani, Ani; Episiasi (Linguistic, English Education and Art (LEEA) Journal, 2025)
This research aimed to investigate the effectiveness of the Problem-Based Learning (PBL) strategy in enhancing students' speaking skills at MAN 1 Lubuklinggau. The study employed a pre-experimental research design using a one-group pre-test and post-test model. A total of 44 students from class XI.1 were selected through cluster sampling. Data were collected using a speaking performance test. The findings revealed that the average pre-test score was 44.59 and increased to 79.77 in the post-test. Statistical analysis using a paired sample t-test showed a t-count of 21.32, which was significantly greater than the t-table value of 2.016 at a 0.05 significance level. These findings support the conclusion that the PBL strategy significantly improves students' speaking skills and fosters a more engaging learning environment. Keywords: Asking and Giving Opinion, Problem-Based Learning Strategy, Senior High School Speaking Skill, Teaching Students.